1992
DOI: 10.3354/meps085163
|View full text |Cite
|
Sign up to set email alerts
|

Variations in carboxylase activity in marine phytoplankton cultures, ß-carbolxylation in carbon flux studies

Abstract: Inorganic carbon may be assimilated through the Calvin-Benson cycle via the enzyme ribulose-1.5-bisphosphate carboxylase (Rubisco) andlor by 0-carboxylation [via the enzymes phosphoenolpyruvate carboxylase (PEPC), phosphoenolpyruvate carboxykinase (PEPCK) or pyruvate carboxylase]. Here, carboxylase activity measurements for marine phytoplankton are described. Two indices measuring carboxylase activity in marine phytoplankton were used. The first measures Rubisco activity per unit chlorophyll [R/Chl; nmol CO2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 26 publications
1
37
0
Order By: Relevance
“…Reinfelder et al (2000) demonstrated that PEPC activity was up-regulated at low CO 2 concentrations in T. weissflogii and that the measured PEPC activities contributed up to 50% to carbon fixation under zinc limitation. Even though the assay applied in their study does not exclude the anaplerotic role of PEPC, which is considered to be involved in the synthesis of amino-acid precursors (Descolas-Gros and Oriol, 1992), the observation that the 14 C labelled C 4 compound malate was so rapidly formed in T. weissflogii (Reinfelder et al, 2000;Morel et al, 2002;McGinn and Morel, 2008) indicates photosynthetic C 4 fixation rather than anaplerotic processes. However, recent studies (e.g.…”
Section: The Role Of C 4 -Like Photosynthesis In Marine Diatomsmentioning
confidence: 94%
“…Reinfelder et al (2000) demonstrated that PEPC activity was up-regulated at low CO 2 concentrations in T. weissflogii and that the measured PEPC activities contributed up to 50% to carbon fixation under zinc limitation. Even though the assay applied in their study does not exclude the anaplerotic role of PEPC, which is considered to be involved in the synthesis of amino-acid precursors (Descolas-Gros and Oriol, 1992), the observation that the 14 C labelled C 4 compound malate was so rapidly formed in T. weissflogii (Reinfelder et al, 2000;Morel et al, 2002;McGinn and Morel, 2008) indicates photosynthetic C 4 fixation rather than anaplerotic processes. However, recent studies (e.g.…”
Section: The Role Of C 4 -Like Photosynthesis In Marine Diatomsmentioning
confidence: 94%
“…The activities of Rubisco and PEPC were determined using 14 C-based assays modified from previous studies (Descolas-Gros and Oriol 1992;MacIntyre et al 1997). The assays measure the rate of 14 C incorporation into organic (acid stable) carbon products following the addition of H 14 CO 2 3 / 14 CO 2 and ribulose bisphosphate (RuBP) or phosphoenolpyruvate (PEP), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to diatoms, dinoflagellates have higher rates of dark respiration relative to growth rate (Geider and Osborne, 1989) -Gros and Oriol, 1992). Whether differences in ␤-carboxylation activity are reflected in p , however, depends on the ultimate fate of CO 2 involved in these reactions (no effect on p if CO 2 is released again shortly after fixation; Raven, 1997) and on fractionation by the carboxylating enzyme.…”
Section: Taxonomic Differences In Fractionationmentioning
confidence: 99%